2020
DOI: 10.1371/journal.pone.0241481
|View full text |Cite
|
Sign up to set email alerts
|

Application of controlled release urea improved grain yield and nitrogen use efficiency: A meta-analysis

Abstract: The application of controlled release urea (CRU) has been proposed as a crucial method to reduce the adverse environmental effects induced by conventional urea (CU). Yet, a systematic and quantitative analysis on how CRU affects staple crop production including wheat ( Triticum aestivum L .), maize ( Zea mays L .), and rice ( Oryza sativa L .) is lacking. Here, a meta-analysis was conducted to determine how CRU influences soil chemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…The present study showed that in the first 109 days of the experiment dissolved organic carbon (DOC) was significantly improved in coated urea treatments in comparison to the control treatment which might be due to readily available organic compounds like plant root exudates, decomposable organic matter, and sloughed off root cap cells (Ghosh et al, 2012). DOC results of the current experiment are also in line with the findings of Zhu et al (2020) who reported significant improvements in DOC as a result of coated urea fertilizers. Several other studies also support the fact that the application of N fertilizers improves DOC and subsequent crop growth and production (Mehmood et al, 2018;Liyuan et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The present study showed that in the first 109 days of the experiment dissolved organic carbon (DOC) was significantly improved in coated urea treatments in comparison to the control treatment which might be due to readily available organic compounds like plant root exudates, decomposable organic matter, and sloughed off root cap cells (Ghosh et al, 2012). DOC results of the current experiment are also in line with the findings of Zhu et al (2020) who reported significant improvements in DOC as a result of coated urea fertilizers. Several other studies also support the fact that the application of N fertilizers improves DOC and subsequent crop growth and production (Mehmood et al, 2018;Liyuan et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The supply of soil nutrients in already fertile soils slightly enhances or even declines the grain yield. Another study revealed a higher yield increase under P-fertilizer application when the soil phosphorous is low [51] and under controlled-release nitrogen application when the SOC content is low [52]. Therefore, it was observed that the N-application in Ethiopia significantly increases crop yield, although the magnitude is affected by several explanatory factors and crop type.…”
Section: Source Of Variation In Yield Responsesmentioning
confidence: 99%
“…The application of controlled-release fertilizers (CRFs) is one way to improve nutrient use efficiency, reduce nitrogen loss, and contribute to minimizing environmental pollution, providing a better compromise among soil fertility, yield, and grain quality [ 20 , 21 , 22 ]. CRFs prove the potential to decrease the fertilizer application rate by 20% or 30% of the recommended value to achieve the same yield [ 23 ].…”
Section: Introductionmentioning
confidence: 99%